Media Pembelajaran Berbasis Webtoon Untuk Menafsirkan Pandangan Pengarang Dalam Novel - Suciati Suciati; Sumarti Sumarti; Iing Sunarti (Universitas Lampung, 2018)
This study was the development of webtoon-based literary learning media. The purpose of this study was to produce media, to test the feasibility of the media, and test the effectiveness of webtoon-based literary learning media to interpret the author's views in the novel Maafkan Aku, Kuala Mesuji written by Fajar for senior high school students. This study used the Research and Development (R D) method referring to the Borg and Gall model. The results of this study were (1) webtoon-based learning media entitled